Multifaceted Marine Peptides and Their Therapeutic Potential - Svetlana V. Guryanova; Tatiana V. Ovchinnikova (Marine Drugs, 2025)
Marine peptides, derived from a great number of aquatic organisms, exhibit a broad spectrum of biological activities that hold a significant therapeutic potential. This article reviews the multifaceted roles of marine peptides, focusing on their antibacterial, antibiofilm, antifungal, antiviral, antiparasitic, cytotoxic, anticancer, immunomodulatory, chemotactic, opsonizing, anti-inflammatory, antiaging, skin-protective, and wound-healing properties. By elucidating mechanisms of their action and highlighting key research findings, this review aims to provide a comprehensive understanding of possible therapeutic applications of marine peptides, underscoring their importance in developing novel drugs as well as in cosmetology, food industry, aquatic and agriculture biotechnology. Further investigations are essential to harness their therapeutic potential and should focus on detailed mechanism studies, large-scale production, and clinical evaluations with a view to confirm their efficacy and safety and translate these findings into practical applications. It is also important to investigate the potential synergistic effects of marine peptide combinations with existing medicines to enhance their efficacy. Challenges include the sustainable sourcing of marine peptides, and therefore an environmental impact of harvesting marine organisms must be considered as well.